Digital Communication Technologies and Their Economic Implications for Nigeria’s Electronics Manufacturing Industry - Afolabi, Adedolapo Isaiah; Afolabi, Adedoyin Daniel; Oamen, Simbiat Sharon (African Journal of Stability and Development (AJSD), 2025)
The nexus between Nigeria's burgeoning digital economy and its nascent electronics manufacturing sector represents a critical frontier for national economic diversification. Driven by a rapidly expanding ICT sector that contributed 9.88% to the nominal GDP in Q4 2021 and a projected digital economy revenue of $18.30 billion by 2026, Nigeria presents a compelling, albeit challenging, landscape for tech-driven industrial growth. This study provides a comprehensive analysis of how digital communication technologies, specifically the rollout of 5G, the adoption of IoT and AI, and the proliferation of e-commerce, are reshaping the electronics manufacturing value chain. The analysis reveals a dual-faceted relationship. On one hand, these technologies offer significant opportunities to enhance operational efficiency, streamline supply chains, and expand market access. The potential for AI to optimise production, IoT to provide real-time logistics visibility, and e-commerce to connect local manufacturers with a vast consumer base is undeniable. On the other hand, the industry is confronted by deep-seated barriers, including a persistent digital infrastructure deficit, a severe skills gap, and a complex, often inconsistent, regulatory environment. The coexistence of 2G, 4G and 5G networks fragments the consumer market and complicates product design and strategy. A high dependency on imported inputs also raises costs and reduces competitiveness. Drawing from a detailed examination of these dynamics, the report synthesises its findings into a set of strategic recommendations. A multi-stakeholder approach is essential, with the government focusing on regulatory harmonisation and public-private partnerships, manufacturers investing in a phased approach to technology adoption and workforce upskilling, and a broader ecosystem promoting collaboration and targeted investment. By addressing these foundational challenges, Nigeria can transition from being a passive consumer of electronics to a competitive producer, thereby achieving its long-term vision of a digital-first industrial economy.